1979
DOI: 10.1159/000198319
|View full text |Cite
|
Sign up to set email alerts
|

Ligation or External Fistulation of the Common Bile Duct in the Rat. II. Intestinal Disaccharidase Activities

Abstract: 72 h after ligation or external fistulation of the common bile duct the activities of maltase, sucrase and lactase in the homogenate of the small intestinal mucosa of the rat were determined. The experiments were performed in connexion with intestinal perfusion studies, and the disaccharidase activities were measured in unperfused intestinal segments as well as in intestinal loops which had previously been perfused with a sucrose-containing solution. After bile duct ligation, the sucrase and maltase activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The work of Bohmer [2] suggests that bile flow into the small bowel lumen has an effect on disaccharidase levels, while the influence of pancreatic secretions on disaccharidase levels cannot be excluded [18,19], We sug gest that the influence of dietary fibre compo nents on disaccharidase levels may reflect changes in bile or pancreatic secretions.…”
Section: Discussionmentioning
confidence: 87%
“…The work of Bohmer [2] suggests that bile flow into the small bowel lumen has an effect on disaccharidase levels, while the influence of pancreatic secretions on disaccharidase levels cannot be excluded [18,19], We sug gest that the influence of dietary fibre compo nents on disaccharidase levels may reflect changes in bile or pancreatic secretions.…”
Section: Discussionmentioning
confidence: 87%
“…Bile flow [4] and pancreatic secretions [26,27] influence disaccharidase levels. Pan creatic proteases may degrade disacchari dases at the brush border [1], Additionally, pancreatic enzymes or bile may release brush border enzymes from the membrane itself [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…McCarthy et al [16] have reported that high fat diets are associated with low disac charidase levels and other studies suggest that bile flow [4] and pancreatic secretions [26,27] influence disaccharidase levels in the small bowel mucosa. It is possible, therefore, that this influence of fat in the diet on disac charidases is due to the stimulation by di etary fat of bile flow [23] and pancreatic secretions [9,10].…”
mentioning
confidence: 99%
“… 64 , 65 The obesity-related gut microbiome was shown to increase intestinal permeability and the secretion of lipopolysaccharide. 65 Similarly, the gut dysregulation observed in cirrhosis is characterized by increased intestinal permeability and endotoxemia 66 , 67 that contribute to chronic inflammation, oxidative stress, and insulin resistance during sarcopenia development and progression.…”
Section: Peculiar Pathogenesis Of Sarcopenia In Patients With Post-na...mentioning
confidence: 99%